DINAMIKA POLITIK HUKUM DALAM PEMENUHAN HAK ATAS KESEHATAN DI INDONESIA - Mardiansyah, Rico (Veritas et Justitia, 2018)
The right to health is widely recognized as basic human rights and consequently it is the state’s duty to guarantee its fulfilment.  The Indonesian government, in realization of this duty, develops and put in place a national health care (insurance) system, which successful working depend on citizens paying equal amount of the premium needed to sustain this public health care system.  However, the same state, in the context of social justice and welfare, provide poor citizens with monetary aid. This article discusses, by using a juridical normative approach, supplemented by an inter-multi disciplinary approach, the political dynamics underpinnings influencing the social or health care system’s implementation.